ANALYZING THE SOURCES OF TECHNICAL EFFICIENCY AMONG HETEROGENEOUS DAIRY FARMS: A QUANTILE REGRESSION APPROACH - Chidmi, B; Solis, D; Cabrera, VE (ANIMAL PRODUCTION, 2011)
Abstract. An unbalanced panel data including 1,151 farm observations from 2004 to 2008 was used to analyze the determinants of technical efficiency (TE) for dairy farms in the State of Wisconsin. To account for farm heterogeneity in our analysis we implemented a two-step framework using a stochastic production frontier and a quantile regression analysis. Our results show that the determinants of TE affect in very specific ways farmers with different levels of TE. This outcome is of significant importance from an empirical point of view. Farmers could use this knowledge to find alternatives to improve their specific level of performance. Additionally, policy makers could use this information to improve the effectiveness of their policies by targeting specific agricultural services and aid to group of farmers with similar levels of TE.Key Words : technical efficiency, dairy farms